Distribution of the Unionida (Bivalvia, Paleoheterodonta) from Argentina and its conservation in the Southern Neotropical Region - Torres, Santiago Hernan; Cao, Luciana Marina; Gutierrez Gregoric, Diego Eduardo; de Lucia, Micaela; Brea, Francisco José; Darrigran, Gustavo Alberto (PLOS ONE)
Bivalves are one of the most representative groups in the Phylum Mollusca, with over 1,100 freshwater species around the world except Antarctica. About 900 of these species belong to the Order Unionida Gray, 1854. In South America, the distributional range of the Unionida includes all countries in the region and extends as far south as the lakes and rivers of Argentinean-Chilean Patagonia. With the aim of generating distribution maps for the different genera of Unionida in Argentina, we consulted the databases of the nation’s main official malacological collections. The data were analyzed and georeferenced using the point-radius method. Spatial analyses were performed with the software Q-GIS 2.16.3 Nødebo using vector layers under the 2007 Argentinean Geodesic Positions reference system. A total 1,833 lots were analyzed, of which it was possible to georeference 1,503. The distribution of Unionida in Argentinean territory was analyzed according to political provinces, Surface Drainage Basins and the Argentinean Protected Areas. Species richness was analyzed using the surface drainage basins of Argentina. We generate distribution maps for each genus and discuss the species threat status and conservation degree in the region. Only six (18%) of the Unionida present in Argentina have been classified by the IUCN, four are Least Concern and two are Data Deficient. This pattern is also valid for all of South America. More than 95% of the distributional range of the Unionida has no protected area. Conservation management is necessary for the preservation of Unionida diversity in southern South America. Fil: Torres, Santiago Hernan. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro de Investigaciones y Transferencia de Santa Cruz. Universidad Tecnológica Nacional. Facultad Regional Santa Cruz. Centro de Investigaciones y Transferencia de Santa Cruz. Universidad Nacional de la Patagonia Austral. Centro de Investigaciones y Transferencia de Santa Cruz; Argentina. Universidad Nacional de La Plata. Facultad ...